Weimar Germany’s foreign policy and the protection of minorities: The case of the German minority in Poland - Thoene, Ulf (Historia Caribe, 2014)
The protection of minorities in Central Europe became a deeply controversial issue in the aftermath of World War One. The presence of a sizeable German minority in what had become Polish territory following the Versailles settlement played into the hands of political extremists on both sides when the German anti-Weimar right and Polish nationalists saw an opportunity to use the minority issue as a tool for revisionism. Whilst acknowledging that certain revisionist objectives were indeed pursued by Weimar governments, this article argues that democratic and republican forces did not use the minority problem as a direct tool for German expansionism in Eastern Europe.